english: english - khadijah; Bahjatul Murtasidin; Sarpin (Faculty of Law, University of Mataram, 2023)
The current condition of Indonesia is being hit by problems of radicalism and terrorism, the problem of terrorism is a universal problem with doctrines under the guise of religion such as al-Qaeda and ISIS. The image of a peaceful Islam has been tarnished by the many acts of intolerance and radicalism carried out by members of other groups in the name of Islam. There are many factors that cause moral damage that arises due to radicalism and terrorism, but there are many ways to prevent it, one of which is the approach of local cultural wisdom because this is a source of strength and moral control that can be implanted to improve attitudes. The purpose of this study is to explore in detail the wisdom of local culture, especially religious leaders and youth, in order to create a moderate, peaceful, and calm society. The method in this research is by reviewing the literature and answering research questions using dictionaries, books, magazines, interpretation bibles, the internet, and other sources. The results obtained in this study are effective strategies to prevent and overcome radicalism and terrorism by developing a community culture based on equality, solidarity, and cooperation. Meanwhile, local wisdom has several informative and educative functions. Contributions to the formation of a harmonious civilization structure, social networks, mutual trust, and interaction norms are important roles in local wisdom and legal culture to overcome radicalization.